Security and Privacy in Mobile Information and Communication Systems 4th International Conference, MobiSec 2012, Frankfurt am Main, Germany, June 25-26, 2012, Revised Selected Papers - Schmidt, Andreas U.; Russello, Giovanni; Krontiris, Ioannis; Lian, Shiguo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the fourth International ICST Conference on Security and Privacy in Mobile Information and Communication Systems (MOBISEC 2012) held in Frankfurt/Main, Germany, in June 2012. The 13 revised full papers were carefully selected from numerous submissions and cover the application layer of security, highlighting the practical importance of security of mobile devices in concrete usages. Contributions to MobiSec 2012 range from treatments on user privacy issues, over mobile application and app security, to mobile identity management, and NFC. With the orientation toward applications, MobiSec is a perfect interface between academia and industry in the field of mobile communications.
Keywords: Computer science; Computer Communication Networks; Computer network architectures; Data protection; Information Systems; Computer Science; Systems and Data Security; Computer System Implementation; Management of Computing and Information Systems; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computers and Society